Analysis of Risk Factors that are Related to Lung Respiratory Symptoms - Mauliku, Novie Elvinawaty; Suhat, .; Mutia, Tri (KnE Life Sciences, 2021)
Lung respiratory symptoms are a collection of symptoms impairment in the functions of pulmonary due to accumulation high concentration of dust particle. The impact of lung respiratory symptoms is pneumoconiosisdisease. 30%-50% of all occupational diseases are because of pneumoconiosis and 40,000 new cases of pneumoconiosis are caused by workplace dust exposure. The aim of the research is to analysis the risk factors related to lung respiratory symptoms in workers in PT. X West Java. The research used a cross-sectional study which was conducted in PT X with 65 respondents selected by proportional random sampling. Data was collected by interview, observation and measuring. The instrument was used in this research is a questionnaire American Thoracic Societ (ATS) standard consisting of 36 respiratory symptoms lung, low volume sampler, thermohigrometer, scale and microtois equipment. There were 55.4% respondents have respiratory symptoms lungs. The statistical results showed significant correlation of respiratory symptoms lungs with levels of dust total (p = 0.0001, PR=2,813), temperature (p=0,007, PR=0,491), humidity (p=0.0001, PR=7,925), and age (p=0,049, PR=0,615), while the daily of exposure (p=0,498, PR=1,853), smoking habit (0.038, PR=1.944), nutritional status (p=0,418, PR=1,211) and disease history (p=0,247, PR=1,879) were not associated with respiratory symptoms lung on workers PT. X West Java. The Respiratory symptoms lung was a symptom that the cause of the environment and the capacity of the worker Keywords: respiratory symptoms lung, dust total levels, temperature, humidity, smoking habit